Form of notification to the property owner of failure to comply with the obligation of selective waste collection. Critical Gloss to the judgment of the Supreme Administrative Court of 11.10.2024, III FSK 1522/22 - Bartosz Namieciński; Dominika Trzeszczoń (Prawo Budżetowe Państwa i Samorządu)
The procedure for determining the waste management fee based on a punitive rate for entities that do not collect waste in a selective manner constitutes interesting legal construct. The purpose of this commentary is to critically address the interpretation of Article 6ka of the Act on Maintaining Cleanliness and Order in Municipalities, as adopted by the Supreme Administrative Court. According to the Court's assessment, it is possible to notify the property owner of a violation of the obligation to sort waste by placing a red sticker on the waste container, warning of improper sorting. Such notification is a necessary condition for proceeding with further actions in this regard. The position presented by the Supreme Administrative Court contradicts the principle of written proceedings in tax law, as expressed in Article 126 of the Tax Ordinance. Furthermore, it unjustifiably breaks with the established case law on this matter. The study uses a dogmatic-legal research method, analyzing legislation, the case law of administrative courts and scholarly literature on the subject.